Study of Lipids Disorder in sera of Patients with Type II Diabetes Mellitus in Diyala - Zuhair Maroof Hussien; Yasmine Sami Nassir; Dawood Salman Al-Azzawi (Journal of Madenat Alelem University College, 2013)
Diabetes mellitus has been known to associate with lipid disorders and cardiovascular complication. This study was carried out to determine the changes in serum lipid profile in type 2 diabetic patients. Lipid profile was measured in sera of thirty males and females type-2 diabetic patients who attend Baqubah Educational Hospital in Diayla province and compared with thirty healthy of matched age and sex, as control group. The result indicate the presence of significant increase in serum TG (p < 0.0001), TC (p < 0.0001), LDL-C (p <0.0001), and VLDL-C (P <0.0001). Serum HDL-C levels were significantly decreased (p < 0.0001) in type 2 diabetic patients. In conclusion several lipid abnormalities were found in type 2 diabetes mellitus.